Novel echocardiographic measures of myocardial work predicts physical performance during prolonged strenuous exercise. (11th May 2022) - Erevik, C; Kleiven, Ø; Froysa, V; Bjorkavoll-Bergseth, M; Hansen, M; Chivulescu, M; Klaebo, LG; Dejgaard, L; Skadberg, Ø; Melberg, T; Urheim, S; Edvardsen, T; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): The North Sea Race, Laerdal Foundation Background: Cardiac function is a major determinant of physical performance. Cardiac function at rest can be assessed by novel echocardiographic parameters of myocardial work. Physical performance can be accurately measured using sensors recording the power output during exercise. There is limited data on the relationship between resting echocardiographic parameters and power measurements during strenuous endurance exercise. The aim of this work was to study the relationship between power output during exercise and echocardiographic parameters of cardiac structure and function at rest, including echocardiographic parameters of myocardial work. Method: Resting echocardiographic parameters of 40 healthy, middle aged, recreational athletes, were compared with power output recordings during two episodes of endurance exercise of different duration and intensity. The first exercise was a cardiopulmonary exercise (CPX) test, which included both a lactate threshold- and a maximal oxygen uptake test. The second exercise was a 91-km mountain bike leisure sport cycling race. Power output was measured on the bikes using power meters. All study subjects were assessed by echocardiography prior to the CPX test. Coronary Computed Tomography Angiography was performed 1-2 weeks after the race to exclude obstructive coronary artery disease. Results: Study participants were 51.1 ±9.7 years old (73 % men), median 10.0 (7.0-21.3) years of endurance training, and a median of 10.0 (5.0-20.0) endurance exercise competitions during the past five years. Both left ventricular mass and left atrial volume were in the upper reference range: 84.0 (77.0-96.0) gram/m2, 32.0 ±8.5 mL/m2, and the left ventricles were mildly dilated; 81.6 (69.1-96.5) mL/m2 (end-diastole). Median exercise duration: CPX: 43 (IQR 40-45) minutes, race: 236 (214-268) minutes. Mean heart rate; CPX: 145 ±11 bpm, race: 154 ± 10 bpm. Maximal oxygen uptake (Vo2 max): 41.6 ±9 ml/min/kg. Mean power output: CPX: 2.9 ±0.5 watt/kg, race: 2.1 ±0.5 watt/kg. There were strong bivariate correlations between left atrial and ventricular volumes and performance parameters (Table 1). Left ventricular global longitudinal strain (LV GLS) was correlated with Vo2 max. The myocardial work parameters global wasted work (GWW) and global work efficiency (GWE) were correlated with all performance parameters except Vo2 max. In multivariable linear regression models, except for VO2 max, GWW was the most consistent and strongest predictor of physical performance in all models (Table 2). Conclusion: The novel echocardiographic parameter of global wasted work (GWW), assessed at rest, was the strongest and most consistent predictor of physical work measured by power meters during prolonged strenuous exercise.